Malek Bennabi and the Study of the Qur’an: Philosophical Dimensions and Methodological Landmarks - El-Mesawi, Mohamed El-Tahir (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2022)
This study is an attempt to uncover the philosophical fundamentals and methodological principles underlying the topics and ideas discussed in Malek Bennabi’s first book The Qur’anic Phenomenon. This book is characterized by two major features. First, it is in the Islamic context a pioneering intellectual and systematic response to the philosophical and methodological challenges which have, in the wake of modernity and post-modernity, faced religion and religious thought in general and Islam in particular, conceptually, axiologically, and institutionally. Second, it contains the grand intellectual themes and central problematics which oriented Bennabi’s thinking on the various issues and subjects he dealt with in his subsequent works. In analyzing and discussing the theses and positions expressed by Bennabi, much attention has been given to historically contextualizing and relating them to the intellectual and philosophical developments that took place in the West with respect to the consequences of modernity and manifestations of postmodernity.